Acid-sensing ion channel 1a is required for mGlu receptor dependent long-term depression in the hippocampus. (May 2017) - Mango, D.; Braksator, E.; Battaglia, G.; Marcelli, S.; Mercuri, N.B.; Feligioni, M.; Nicoletti, F.; Bashir, Z.I.; Nisticò, R.
Graphical abstract: Abstract: Acid-sensing ion channels (ASICs), members of the degenerin/epithelial Na + channel superfamily, are widely distributed in the mammalian nervous system. ASIC1a is highly permeable to Ca 2+ and are thought to be important in a variety of physiological processes, including synaptic plasticity, learning and memory. To further understand the role of ASIC1a in synaptic transmission and plasticity, we investigated metabotropic glutamate (mGlu) receptor-dependent long-term depression (LTD) in the hippocampus. We found that ASIC1a channels mediate a component of LTD in P30-40 animals, since the ASIC1a selective blocker psalmotoxin-1 (PcTx1) reduced the magnitude of LTD induced by application of the group I mGlu receptor agonist (S)-3, 5-Dihydroxyphenylglycine (DHPG) or induced by paired-pulse low frequency stimulation (PP-LFS). Conversely, PcTx1 did not affect LTD in P13-18 animals. We also provide evidence that ASIC1a is involved in group I mGlu receptor-induced increase in action potential firing. However, blockade of ASIC1a did not affect DHPG-induced polyphosphoinositide hydrolysis, suggesting the involvement of some other molecular partners in the functional crosstalk between ASIC1a and group I mGlu receptors. Notably, PcTx1 was able to prevent the increase in GluA1 S845 phosphorylation at the post-synaptic membrane induced by group I mGlu receptor activation. These findings suggest a novel function of ASIC1a channels in the regulation of group I mGlu receptor synaptic plasticity and intrinsic excitability.